Porous sealing gasket with high elastic recovery rate and preparation method thereof

By using stereoselective anion polymerization in the sealing gasket to generate fluorine-containing copolymers in a high cis configuration, combined with porous structure and special processing technology, the shortcomings of traditional sealing gaskets in elastic recovery, chemical resistance and high temperature resistance are solved, and a high-performance and high-reliability sealing gasket is achieved.

CN119735851AActive Publication Date: 2025-04-01CIXI AIFLON SEALING MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510258801.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-01
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

Traditional sealing gaskets have shortcomings in elastic recovery, chemical resistance and high temperature resistance, and have complex processing technology, low production efficiency and high cost, making it difficult to meet the needs of high-performance and high-reliability applications.

Method used

Three-channel microreactor is used to perform stereoselective anion polymerization to generate fluorine-containing copolymers in a high cis configuration. By introducing fluorinated graphene and supercritical CO2 foaming agent, a porous structure is formed, combining dynamic vulcanization and plasma surface fluorination treatment to optimize the microstructure and performance of the material.

Benefits of technology

It significantly improves the elastic recovery rate, chemical resistance and high temperature resistance of the sealing gasket, enhances the mechanical properties and thermal stability of the material, and meets the requirements of long-term durability and stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous sealing gasket with a high elastic recovery rate. The preparation method comprises the following steps: S1, respectively dissolving fluorine-containing olefin, 1, 1, 1, 3, 3, 3-hexafluoro-2-propyleneimine and an initiator in a solvent; s2, inputting the mixture into a three-channel microreactor, and carrying out low-temperature polymerization to generate a fluorine-containing copolymer; s3, introducing fluorinated graphene of which the surface is grafted with an RAFT chain transfer agent at a polymerization reaction outlet, and applying a shearing rate through a conical runner; s4, the product and natural rubber are compounded into composite colloid, the composite colloid is injected into a mold, dynamic vulcanization is conducted, and a supercritical CO2 foaming agent is synchronously introduced; and S5, after demolding, plasma surface fluorination treatment and hot-pressing shaping are sequentially carried out, and the porous sealing gasket is obtained. According to the preparation method, the high elastic recovery rate of the sealing gasket is achieved, and the sealing gasket has excellent chemical resistance and high temperature resistance and can meet the requirements for long-term durability and stability in the application fields of spaceflight, automobiles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealing gaskets, and in particular to a porous sealing gasket with a high elastic recovery rate and a preparation method thereof. Background Art

[0002] In the field of sealing gaskets, traditional materials such as natural rubber, nitrile rubber and silicone rubber are widely used. However, these materials have many limitations in practical applications. For example, although natural rubber has good elastic recovery ability, its chemical resistance and high temperature resistance are poor, and it is difficult to meet the use requirements under complex working conditions. Although nitrile rubber has good oil resistance, its elastic recovery ability is insufficient and it is easy to cause permanent deformation during repeated compression and release. Silicone rubber performs well in high and low temperature resistance, but its mechanical strength and elastic recovery ability still need to be improved.

[0003] In addition, traditional sealing gaskets have microstructural inhomogeneities, which lead to stress concentration and further affect the overall performance of the material. In terms of processing technology, traditional preparation methods usually require multiple complex processes with low production efficiency and high cost. These problems limit the use of sealing gaskets in high-performance, high-reliability applications, especially in aerospace, automotive industry, and chemical equipment, which put forward higher requirements on the comprehensive performance of sealing materials. Therefore, the development of a sealing gasket material that can simultaneously meet the requirements of high elastic recovery, chemical resistance, and high temperature resistance has become an important direction of current research. Summary of the invention

[0004] In view of the above shortcomings of the prior art, the present invention provides a method for preparing a porous sealing gasket with a high elastic recovery rate to solve the shortcomings of traditional sealing gaskets in elastic recovery ability, chemical resistance and high temperature resistance, while optimizing its microstructure and processing technology, thereby improving its comprehensive performance and meeting the requirements of long-term durability and stability.

[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is: A method for preparing a porous sealing gasket with a high elastic recovery rate, the method comprising the following steps: S1: dissolving fluorinated olefin, 1,1,1,3,3,3-hexafluoro-2-propyleneimine and an initiator in a solvent in proportion to obtain a first raw material liquid, a second raw material liquid and a third raw material liquid; S2: The first raw material liquid, the second raw material liquid and the third raw material liquid obtained in step S1 are input into a three-channel microreactor, the reaction temperature is controlled to be -20°C to -15°C, the residence time is 8 to 10 minutes, and a fluorinated copolymer is generated by stereoselective anionic polymerization; step S2 of the present invention performs stereoselective anionic polymerization under low temperature conditions, and the generated fluorinated copolymer has a high cis configuration ratio, which can significantly improve the elastic recovery ability of the polymer. At the same time, by reacting fluorinated olefins and 1,1,1,3,3,3-hexafluoro-2-propylene imine as monomers, due to the high hydrophobicity and low polarity of the trifluoromethyl and perfluoroalkyl segments introduced into 1,1,1,3,3,3-hexafluoro-2-propylene imine, not only the chemical resistance and thermal stability of the fluorinated copolymer are further improved, but also the synergistic effect with the fluorinated groups in the fluorinated olefins makes the porous sealing gasket prepared by the present invention have excellent chemical resistance, high temperature resistance and mechanical properties.

[0006] S3: Introduce fluorinated graphene with surface grafted RAFT chain transfer agent at the polymerization outlet of the three-channel microreactor in step S2, and apply a shear rate of 500-800s through the conical flow channel -1 , so that the FGN is oriented along the stretching direction; step S3 of the present invention enhances the mechanical properties and thermal stability of the polymer by introducing fluorinated graphene with a surface grafted RAFT chain transfer agent. The shear rate is applied through the conical flow channel to orientedly align the FGN along the stretching direction, thereby improving the orientation degree of the material and enhancing the anisotropic performance of the material.

[0007] S4: Compound the polymer obtained in step S3 with natural rubber to form a composite colloid, inject it into the mold, dynamically vulcanize it at 170-180°C and 4-6MPa, and then introduce a supercritical CO2 foaming agent to perform a foaming operation; step S4 of the present invention forms a three-dimensional interconnected porous structure through the simultaneous use of dynamic vulcanization and supercritical CO2 foaming agent. The porous structure helps to improve the elastic recovery rate of the material while maintaining good compression performance. Compounding the fluorine-containing copolymer with natural rubber combines the high elasticity of natural rubber and the chemical resistance of the fluorine-containing copolymer, further optimizing the comprehensive performance of the material. By forming a porous structure, the material has higher molecular chain activity at room temperature, thereby improving the elastic recovery ability. At the same time, the formation of the porous structure helps to reduce stress concentration and further optimize the elastic recovery ability of the material.

[0008] S5: After demolding, plasma surface fluorination treatment and hot pressing shaping are carried out in sequence to obtain a porous sealing gasket with a high elastic recovery rate. Step S5 of the present invention not only enhances the chemical resistance and thermal stability of the material surface through plasma surface fluorination treatment, but also optimizes the surface properties of the material, ensures the uniformity of the microstructure of the material, avoids permanent deformation caused by stress concentration, and thus improves the elastic recovery ability of the material. Hot pressing shaping further ensures the dimensional stability and shape retention ability of the material, thereby improving the overall comprehensive performance of the material, so that it can meet the requirements of long-term durability and stability.

[0009] As a preferred technical solution, the fluorinated olefin is composed of (3E)-1,1,2-trifluoro-1,3-pentadiene and perfluoroolefin ether. The high flexibility and low glass transition temperature (Tg) of the perfluoroether segment in the perfluoroolefin ether of the present invention significantly improve the elastic recovery of the polymer, while enhancing the chemical resistance and thermal stability of the material. In addition, the introduction of (3E)-1,1,2-trifluoro-1,3-pentadiene further improves the thermal stability and mechanical properties of the polymer and optimizes the crystallization properties of the polymer; its unique cis configuration contributes to the regular arrangement of the polymer chain, so that it can still maintain good flexibility and elastic recovery at low temperatures.

[0010] As a preferred technical solution, the perfluoroolefin ether is perfluoroethyl vinyl ether and / or perfluoro-n-propyl vinyl ether.

[0011] As a preferred technical solution, the initiator is a composite system of tert-butyl lithium and a chiral boron catalyst, with a molar ratio of 1:0.02 to 0.05. In the present invention, tert-butyl lithium, as a strong alkaline initiator, can efficiently initiate the polymerization reaction of fluorinated olefins and 1,1,1,3,3,3-hexafluoro-2-propylene imine, providing highly active polymerization sites. The chiral boron catalyst precisely regulates the stereo configuration of the polymer chain through its unique catalytic mechanism to ensure that the generated fluorinated copolymer has a high cis configuration ratio. The synergistic effect of the two makes this high cis configuration not only significantly improve the elastic recovery ability of the polymer, but also optimizes the regularity and crystallization properties of the polymer chain.

[0012] As a preferred technical solution, in step S2, the channel material of the three-channel microreactor is silicon nitride ceramic, the channel cross-section is a 200μm×500μm rectangular structure, and the Reynolds number Re is controlled within the range of 40 to 80. The present invention uses a three-channel microreactor for polymerization reaction, which not only improves the reaction efficiency and stability, but also ensures the uniform distribution of polymer chains and reduces stress concentration points. This uniformity helps to improve the overall performance of the material, especially the elastic recovery ability.

[0013] As a preferred technical solution, the fluorinated graphene with a RAFT chain transfer agent grafted on the surface is prepared by the following steps: first, the fluorinated graphene is dispersed in dimethyl sulfoxide, then a RAFT chain transfer agent is added, and a grafting reaction is carried out under nitrogen protection to obtain the fluorinated graphene with a RAFT chain transfer agent grafted on the surface.

[0014] As a preferred technical solution, in step S4, the injection rate of the supercritical CO2 foaming agent is 0.5-1.0 mL / min.

[0015] As a preferred technical solution, di-tert-butyl peroxyisopropylbenzene is used as a dynamic cross-linking agent in the dynamic vulcanization process.

[0016] As a preferred technical solution, in step S5, the process parameters of the plasma surface fluorination treatment are: power 200-300 W, treatment time 10-15 minutes, and the fluorination gas is a mixture of CF4 and Ar.

[0017] Another aspect of the present invention is to provide a porous sealing gasket with a high elastic recovery rate, wherein the porous sealing gasket is prepared by the above-mentioned method for preparing a porous sealing gasket with a high elastic recovery rate.

[0018] Beneficial effects of the present invention: The method for preparing a porous sealing gasket with high elastic recovery rate of the present invention not only achieves a high elastic recovery rate of the sealing gasket, but also achieves excellent chemical resistance and high temperature resistance by innovatively introducing a high cis-configuration fluorinated copolymer and fluorinated graphene into the polymer chain. This design not only enhances the mechanical properties of the material, but also maintains good flexibility and elastic recovery ability, helps to reduce stress concentration, and further optimizes the overall performance of the material.

[0019] In general, the porous sealing gasket with high elastic recovery rate of the present invention not only has excellent elastic recovery ability and chemical resistance, but also has good high temperature resistance and mechanical strength, which can meet the long-term durability and stability requirements of sealing gaskets in high-performance application fields such as aerospace and automotive industries. DETAILED DESCRIPTION

[0020] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0021] Example 1 The method for preparing a porous sealing gasket with high elastic recovery rate in this embodiment comprises the following steps: S1: 36 g of fluorinated olefin (composed of 22 g of (3E)-1,1,2-trifluoro-1,3-pentadiene and 14 g of perfluoroethyl vinyl ether), 12 g of 1,1,1,3,3,3-hexafluoro-2-propyleneimine and 0.05 g of initiator were respectively dissolved in 100 mL of dimethyl sulfoxide solvent of the same volume to obtain a first raw material liquid, a second raw material liquid and a third raw material liquid; the initiator was a composite system of tert-butyl lithium and a chiral boron catalyst (diisopinocampheyl chloroborane) in a molar ratio of 1:0.02.

[0022] S2: The first raw material liquid, the second raw material liquid and the third raw material liquid obtained in step S1 are input into a three-channel microreactor at a flow rate of 0.2 mL / min, the reaction temperature is controlled to be -15°C, the residence time is 10 minutes, and a fluorinated copolymer is generated by stereoselective anionic polymerization. The channel material of the three-channel microreactor is silicon nitride ceramic, the channel cross-section is a 200 μm×500 μm rectangular structure, and the Reynolds number Re is controlled in the range of 40 to 80.

[0023] S3: 0.5 g of fluorinated graphene (FGN) with surface grafted RAFT chain transfer agent was introduced into the polymerization outlet of the three-channel microreactor in step S2, and a shear rate of 500 s was applied through the conical flow channel. -1 , so that the FGN is oriented along the stretching direction.

[0024] S4: Compound the polymer obtained in step S3 with natural rubber in a mass ratio of 3:2 to form a composite colloid, inject it into the mold, dynamically vulcanize it at 170°C and 5MPa for 15 minutes, and then introduce a small amount of supercritical CO2 foaming agent for 5 minutes of foaming operation. 0.15g of di-tert-butyl peroxyisopropylbenzene is used as a dynamic crosslinking agent during the dynamic vulcanization process. The injection rate of the supercritical CO2 foaming agent is 0.5 mL / min. The pressure of the supercritical CO2 foaming agent is 10MPa and the temperature is 35°C.

[0025] S5: After demoulding, plasma surface fluorination treatment and hot pressing are carried out in sequence to obtain a porous sealing gasket with high elastic recovery rate. The process parameters of plasma surface fluorination treatment are: power 300W, treatment time 10 minutes, fluorination gas is a mixed gas of CF4 and Ar (volume ratio 1:3). The hot pressing temperature is 180°C, the pressure is 8MPa, and the time is 30 minutes.

[0026] The surface-grafted fluorinated graphene with a RAFT chain transfer agent is prepared by the following steps: first, 1 gram of fluorinated graphene is weighed, dispersed in 50 milliliters of dimethyl sulfoxide (DMSO), and ultrasonically treated for 30 minutes to ensure uniform dispersion. Subsequently, 0.5 grams of RAFT chain transfer agent (2-cyano-5-hydroxy-2-pentylbenzene dithiocarboxylate) is added, and the grafting reaction is carried out under nitrogen protection, the reaction temperature is controlled at 80°C ± 5°C, and the reaction time is 12 hours. After the reaction is completed, the reaction mixture is cooled to room temperature, the solid product is collected by centrifugation, and washed 3 times with anhydrous ethanol to remove the unreacted RAFT chain transfer agent and impurities, and finally vacuum dried at 60°C for 12 hours to obtain the surface-grafted fluorinated graphene with a RAFT chain transfer agent.

[0027] Example 2 The method for preparing a porous sealing gasket with high elastic recovery rate in this embodiment comprises the following steps: S1: 40 g of fluorinated olefin (composed of 26 g of (3E)-1,1,2-trifluoro-1,3-pentadiene and 14 g of perfluoro-n-propyl vinyl ether), 15 g of 1,1,1,3,3,3-hexafluoro-2-propyleneimine and 0.05 g of initiator were dissolved in 100 mL of dimethyl sulfoxide solvent of the same volume to obtain a first raw material liquid, a second raw material liquid and a third raw material liquid; the initiator was a composite system of tert-butyl lithium and a chiral boron catalyst (diisopinocampheyl chloroborane) in a molar ratio of 1:0.03.

[0028] S2: The first raw material liquid, the second raw material liquid and the third raw material liquid obtained in step S1 are input into a three-channel microreactor at a flow rate of 0.25 mL / min, the reaction temperature is controlled to be -15°C, the residence time is 8 minutes, and a fluorinated copolymer is generated by stereoselective anionic polymerization. The channel material of the three-channel microreactor is silicon nitride ceramic, the channel cross-section is a 200 μm×500 μm rectangular structure, and the Reynolds number Re is controlled in the range of 40 to 80.

[0029] S3: 0.6 g of surface-grafted RAFT chain transfer agent fluorinated graphene (FGN) was introduced into the polymerization outlet of the three-channel microreactor in step S2, and a shear rate of 600 s was applied through the conical flow channel. -1 , so that the FGN is oriented along the stretching direction.

[0030] S4: Compound the polymer obtained in step S3 with natural rubber in a mass ratio of 3:2 to form a composite colloid, inject it into the mold, dynamically vulcanize it at 175°C and 6MPa for 15 minutes, and then introduce a small amount of supercritical CO2 foaming agent for 5 minutes of foaming operation. 0.15g of di-tert-butyl peroxyisopropylbenzene is used as a dynamic crosslinking agent during the dynamic vulcanization process. The injection rate of the supercritical CO2 foaming agent is 0.7mL / min. The pressure of the supercritical CO2 foaming agent is 10MPa and the temperature is 35°C.

[0031] S5: After demoulding, plasma surface fluorination treatment and hot pressing are carried out in sequence to obtain a porous sealing gasket with high elastic recovery rate. The process parameters of plasma surface fluorination treatment are: power 250W, treatment time 12 minutes, fluorination gas is a mixed gas of CF4 and Ar (volume ratio 1:3). The hot pressing temperature is 180°C, the pressure is 8MPa, and the time is 30 minutes.

[0032] The fluorinated graphene with the surface grafted RAFT chain transfer agent is the same as that in Example 1.

[0033] Example 3 The method for preparing a porous sealing gasket with high elastic recovery rate in this embodiment comprises the following steps: S1: 45 g of fluorinated olefin (composed of 30 g of (3E)-1,1,2-trifluoro-1,3-pentadiene and 15 g of perfluoroethyl vinyl ether), 18 g of 1,1,1,3,3,3-hexafluoro-2-propyleneimine and 0.05 g of initiator were respectively dissolved in 100 mL of dimethyl sulfoxide solvent of the same volume to obtain a first raw material liquid, a second raw material liquid and a third raw material liquid; the initiator was a composite system of tert-butyl lithium and a chiral boron catalyst (diisopinocampheyl chloroborane) in a molar ratio of 1:0.05.

[0034] S2: The first raw material liquid, the second raw material liquid and the third raw material liquid obtained in step S1 are input into a three-channel microreactor at a flow rate of 0.3 mL / min, the reaction temperature is controlled to be -20°C, the residence time is 8 minutes, and a fluorinated copolymer is generated by stereoselective anionic polymerization. The channel material of the three-channel microreactor is silicon nitride ceramic, the channel cross-section is a 200 μm×500 μm rectangular structure, and the Reynolds number Re is controlled in the range of 40 to 80.

[0035] S3: 0.7 g of surface-grafted RAFT chain transfer agent fluorinated graphene (FGN) was introduced into the polymerization outlet of the three-channel microreactor in step S2, and a shear rate of 800 s was applied through the conical flow channel. -1 , so that the FGN is oriented along the stretching direction.

[0036] S4: The polymer obtained in step S3 is compounded with natural rubber in a mass ratio of 3:2 to form a composite colloid, which is injected into a mold, and dynamically vulcanized at 180°C and 6MPa for 15 minutes, and then a small amount of supercritical CO2 foaming agent is introduced for 5 minutes of foaming operation. 0.15g of di-tert-butyl peroxyisopropylbenzene is used as a dynamic crosslinking agent during the dynamic vulcanization process. The injection rate of the supercritical CO2 foaming agent is 1.0 mL / min. The pressure of the supercritical CO2 foaming agent is 10MPa and the temperature is 35°C.

[0037] S5: After demoulding, plasma surface fluorination treatment and hot pressing are carried out in sequence to obtain a porous sealing gasket with high elastic recovery rate. The process parameters of plasma surface fluorination treatment are: power 300W, treatment time 10 minutes, fluorination gas is a mixed gas of CF4 and Ar (volume ratio 1:3). The hot pressing temperature is 180°C, the pressure is 8MPa, and the time is 30 minutes.

[0038] The fluorinated graphene with the surface grafted RAFT chain transfer agent is the same as that in Example 1.

[0039] Comparative Example 1 The raw material composition and preparation steps of the method for preparing a porous sealing gasket with a high elastic recovery rate in this comparative example are basically the same as those in Example 1, except that in the preparation method of this comparative example, the fluorinated olefin is only (3E)-1,1,2-trifluoro-1,3-pentadiene.

[0040] Comparative Example 2 The raw material composition and preparation steps of the method for preparing a porous sealing gasket with high elastic recovery rate in this comparative example are basically the same as those in Example 1, except that in the preparation method of this comparative example, the fluorinated olefin is only perfluoroethyl vinyl ether.

[0041] Comparative Example 3 The raw material composition and preparation steps of the method for preparing a porous sealing gasket with high elastic recovery rate in this comparative example are basically the same as those in Example 1, except that in the preparation method of this comparative example, the initiator is only tert-butyl lithium.

[0042] Comparative Example 4 The raw material composition and preparation steps of the method for preparing a porous sealing gasket with a high elastic recovery rate in this comparative example are basically the same as those in Example 1, except that, in the preparation method of this comparative example, step S3 is omitted.

[0043] The porous sealing gaskets prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to performance tests, and the performance results are shown in Table 1: Among them, the test of elastic recovery rate is based on GB / T 528 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The specific test conditions are: the sample is stretched to 300% strain and then released, and the elastic recovery rate is calculated by measuring the length change after recovery. This indicator reflects the ability of the material to return to its original state after stretching. The higher the value, the stronger the elastic recovery ability of the material.

[0044] The test of compression set rate is based on GB / T 7757 "Determination of compressive stress-strain properties of vulcanized rubber or thermoplastic rubber". The specific test conditions are: keep the sample at 150°C for 70 hours, and the compression rate is 25%. The material's resistance to deformation is evaluated by measuring the degree of permanent deformation after compression. The lower the value, the better the dimensional stability of the material under high temperature and high pressure.

[0045] The test of thermal stability is based on GB / T 1634 "Determination of load deformation temperature of plastics". The specific test conditions are: heating rate of 2℃ / min, load of 0.45 MPa. The thermal deformation temperature of the material under the specified load is measured by a thermal deformation tester. The higher the value, the better the high temperature resistance of the material.

[0046] The chemical resistance test is based on ISO 1817 "Rubber or thermoplastic elastomer - Determination of resistance to liquids". The specific test conditions are: immerse the sample in 30% sulfuric acid, 30% sodium hydroxide and toluene, and keep it at room temperature for 7 days. The chemical resistance of the sample is evaluated by observing the performance changes of the sample in different chemical media. The results are divided into grades such as "excellent", "good" and "fair". The higher the value or the higher the grade, the better the chemical resistance of the material.

[0047] Table 1 project Elastic recovery rate, % Compression set rate, % Thermal stability, °C Chemical resistance Example 1 98 7 318 Excellent Example 2 97 8 314 Excellent Example 3 98 6 320 Excellent Comparative Example 1 87 12 286 good Comparative Example 2 92 9 292 good Comparative Example 3 91 10 304 good Comparative Example 4 96 12 282 Excellent The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A method for preparing a porous sealing gasket with high elastic recovery rate, characterized in that: The preparation method comprises the following steps: S1: dissolving fluorinated olefin, 1,1,1,3,3,3-hexafluoro-2-propyleneimine and an initiator in a solvent in proportion to obtain a first raw material liquid, a second raw material liquid and a third raw material liquid; S2: The first raw material solution, the second raw material solution and the third raw material solution obtained in step S1 are input into a three-channel microreactor, the reaction temperature is controlled to be -20°C to -15°C, the residence time is 8 to 10 minutes, and a fluorinated copolymer is generated by stereoselective anionic polymerization; S3: Introduce fluorinated graphene with surface grafted RAFT chain transfer agent at the polymerization outlet of the three-channel microreactor in step S2, and apply a shear rate of 500-800s through the conical flow channel -1 , so that the FGN is oriented along the stretching direction; S4: Compounding the polymer obtained in step S3 with natural rubber to form a composite colloid, injecting it into a mold, dynamically vulcanizing it at 170-180° C. and 4-6 MPa, and then introducing a supercritical CO2 foaming agent for foaming operation; S5: After demoulding, plasma surface fluorination treatment and hot pressing are performed in sequence to obtain a porous sealing gasket with a high elastic recovery rate.

2. The method for preparing a porous sealing gasket with high elastic recovery rate according to claim 1, characterized in that: The fluorinated olefins consist of (3E)-1,1,2-trifluoro-1,3-pentadiene and perfluoroolefin ether.

3. The method for preparing a porous sealing gasket with high elastic recovery rate as claimed in claim 2, characterized in that: The perfluoroolefin ether is perfluoroethyl vinyl ether and / or perfluoro-n-propyl vinyl ether.

4. The method for preparing a porous sealing gasket with high elastic recovery rate according to claim 1, characterized in that: The initiator is a composite system of tert-butyl lithium and a chiral boron catalyst, and the molar ratio is 1:0.02-0.

05.

5. The method for preparing a porous sealing gasket with high elastic recovery rate according to claim 1, characterized in that: In the step S2, the channel material of the three-channel microreactor is silicon nitride ceramic, the channel cross section is a 200 μm×500 μm rectangular structure, and the Reynolds number Re is controlled within the range of 40 to 80.

6. The method for preparing a porous sealing gasket with high elastic recovery rate according to claim 1, characterized in that: The fluorinated graphene with a RAFT chain transfer agent grafted on the surface is prepared by the following steps: firstly, dispersing the fluorinated graphene in dimethyl sulfoxide, then adding a RAFT chain transfer agent, and performing a grafting reaction under nitrogen protection to obtain the fluorinated graphene with a RAFT chain transfer agent grafted on the surface.

7. The method for preparing a porous sealing gasket with high elastic recovery rate according to claim 1, characterized in that: In step S4, the injection rate of the supercritical CO2 foaming agent is 0.5-1.0 mL / min.

8. The method for preparing a porous sealing gasket with high elastic recovery rate as claimed in claim 1, characterized in that: In the dynamic vulcanization process, di-tert-butyl peroxyisopropylbenzene is used as a dynamic crosslinking agent.

9. The method for preparing a porous sealing gasket with high elastic recovery rate according to claim 1, characterized in that: In step S5, the process parameters of the plasma surface fluorination treatment are: power 200-300W, treatment time 10-15 minutes, and the fluorination gas is a mixed gas of CF4 and Ar.

10. A porous sealing gasket with high elastic recovery rate, characterized in that: The porous sealing gasket is prepared by the method for preparing a porous sealing gasket with high elastic recovery rate according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Functionalised graphene

    CN103003197A

  • Perfluoroether elastomer as well as preparation method and application thereof

    CN115368495A

  • Polyvinyl fluoride / fluorinated graphene composite material and forming method thereof

    CN116589809A

  • Preparation method of perfluoroether elastomer composition

    CN117362873A

  • Microporous fluoroelastomer compositions and methods of making same

    CN117866273A